Impacts of Land Use Change on the Regional Climate: A Structural Equation Modeling Study in Southern China - Zhanqi Wang; Bingqing Li; Jun Yang (Advances in Meteorology)
With the frequent human activities operating on the earth, the impacts of land use change on the regional climate are increasingly perceptible. Under the background of the rapid urbanization, understanding the impacts of land use change on the regional climate change is vital and significant. In this study, we investigated the relationships between land use change and regional climate change through a structural equation model. Southern China was selected as the study area for its rapid urbanization and different structure of land use among its counties. The results indicate that the path coefficients of “vegetation,” “Urban and surrounding area,” and “other” to “climate” are −0.42, 0.20, and 0.46, respectively. Adding vegetation area is the main method to mitigate regional climate change. Urban and surrounding area and other areas influence regional climate by increasing temperature and precipitation to a certain extent. Adding grassland and forestry, restraining sprawl of built-up area, and making the most use of unused land are efficient ways to mitigate the regional climate change in Southern China. The results can provide feasible recommendations to land use policy maker.